Pengaruh Pelayanan Kualitas Pelaksanaan Sistem Penerimaan Murid Baru (SPMB) Terhadap Kepuasan Peserta Tahun 2025: The Effect of Service Quality in the Implementation of the New Student Admission System (SPMB) on Participant Satisfaction in 2025 - Muhammad Adhi Nugroho; Muhammad Rafi Sakhi Rahman; Muhammad Chandra Hisyam; Siti Alya; Astrid Annisa Fauziah; Rudianto Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the influence of Service Quality in the Implementation of SPMB, measured through the aspects of System Ease, System Speed, Technical Support, Customer Service Support, and Socialization, on Participant Satisfaction in 2025. This quantitative research utilized evaluation survey data from 528 respondents distributed across various Regencies/Cities/Provinces in Indonesia. The data was processed using Multiple Linear Regression Analysis. The F-test results indicate that SPMB Service Quality simultaneously has a significant influence on Participant Satisfaction. The coefficient of determination (Adjusted R Square) of 0.652 shows that 65.2% of the variation in Participant Satisfaction is explained by the model. Partially, four variables (System Ease, System Speed, Technical Support, and Socialization) have a significant influence (Sig. 0.000), while the Customer Service Support variable does not have a significant influence (Sig. > 0.110). It is concluded that continuous improvements in system performance and technical support are strategic keys to increasing SPMB Participant Satisfaction.